Much Ado About Nothing? : Estimating the Impact of a U.S. Slowdown on Thai Growth - Aiyar, Shekhar (IMF Working Papers; Working Paper ;, 2008)
External demand was the main driver of growth in Thailand in 2006 and 2007. However, WEO projections indicate moderating foreign demand in 2008, with U.S. growth being revised downwards to reflect the turmoil in housing and credit markets, and high oil prices. While the share of Thai exports to the US has fallen in recent years, the US remains Thailand's largest export destination. We use a small structural model and Bayesian estimation to assess the possible impact of a U.S. slowdown on Thai growth. We find that a 1 percent slowdown in U.S. growth in 2008-relative to the baseline forecast-could have an upper-bound impact on Thai GDP growth of 0.9 percentage points.